Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve the expression [tex]\((8 - 3i) - (8 - 3i)(8 + 8i)\)[/tex], let's go through the steps in detail.
1. Calculate [tex]\((8 - 3i)(8 + 8i)\)[/tex]:
- Use the distributive property (also known as FOIL for binomials): [tex]\((a + bi)(c + di) = ac + adi + bci + bdi^2\)[/tex].
- For the given expression:
[tex]\[(8 - 3i)(8 + 8i)\][/tex]
[tex]\[ = 8 \cdot 8 + 8 \cdot 8i - 3i \cdot 8 - 3i \cdot 8i \][/tex]
- Calculate each component:
[tex]\[ = 64 + 64i - 24i - 24i^2 \][/tex]
[tex]\[ = 64 + 64i - 24i - 24(-1) \quad \text{(since } i^2 = -1 \text{)} \][/tex]
[tex]\[ = 64 + 64i - 24i + 24 \][/tex]
[tex]\[ = (64 + 24) + (64i - 24i) \][/tex]
[tex]\[ = 88 + 40i \][/tex]
2. Subtract [tex]\((8 - 3i)\)[/tex] from the result obtained:
[tex]\[ (8 - 3i) - (88 + 40i) \][/tex]
- Separate the real and imaginary parts:
[tex]\[ = (8 - 88) + (-3i - 40i) \][/tex]
[tex]\[ = -80 - 43i \][/tex]
Thus, the value of the expression [tex]\((8 - 3i) - (8 - 3i)(8 + 8i)\)[/tex] is [tex]\(-80 - 43i\)[/tex].
The correct answer is:
B. [tex]\(-80 - 43i\)[/tex]
1. Calculate [tex]\((8 - 3i)(8 + 8i)\)[/tex]:
- Use the distributive property (also known as FOIL for binomials): [tex]\((a + bi)(c + di) = ac + adi + bci + bdi^2\)[/tex].
- For the given expression:
[tex]\[(8 - 3i)(8 + 8i)\][/tex]
[tex]\[ = 8 \cdot 8 + 8 \cdot 8i - 3i \cdot 8 - 3i \cdot 8i \][/tex]
- Calculate each component:
[tex]\[ = 64 + 64i - 24i - 24i^2 \][/tex]
[tex]\[ = 64 + 64i - 24i - 24(-1) \quad \text{(since } i^2 = -1 \text{)} \][/tex]
[tex]\[ = 64 + 64i - 24i + 24 \][/tex]
[tex]\[ = (64 + 24) + (64i - 24i) \][/tex]
[tex]\[ = 88 + 40i \][/tex]
2. Subtract [tex]\((8 - 3i)\)[/tex] from the result obtained:
[tex]\[ (8 - 3i) - (88 + 40i) \][/tex]
- Separate the real and imaginary parts:
[tex]\[ = (8 - 88) + (-3i - 40i) \][/tex]
[tex]\[ = -80 - 43i \][/tex]
Thus, the value of the expression [tex]\((8 - 3i) - (8 - 3i)(8 + 8i)\)[/tex] is [tex]\(-80 - 43i\)[/tex].
The correct answer is:
B. [tex]\(-80 - 43i\)[/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.